1997
DOI: 10.1128/jb.179.5.1704-1713.1997
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Tn5 transposase overproduction phenotype in Escherichia coli and localization of a suppressor of transposase overproduction killing that is an allele of rpoH

Abstract: Tn5 transposase (Tnp) overproduction is lethal to Escherichia coli. Tnp overproduction causes cell filamentation, abnormal chromosome segregation, and an increase in anucleated cell formation. There are two simple explanations for the observed phenotype: induction of the SOS response or of the heat shock response. The data presented here show that overproduction of Tnp neither induces an SOS response nor a strong heat shock response. However, our experiments do indicate that induction of some 32 -programmed fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Observations were made according to Yigit and Reznikoff [1997]. Briefly, bacteria were collected and resuspended in sterile saline (0.9% NaCl in H 2 O), spread onto glass slides, then air-dried and fixed with 100% methanol.…”
Section: Microscopic Observation Of Bacteriamentioning
confidence: 99%
“…Observations were made according to Yigit and Reznikoff [1997]. Briefly, bacteria were collected and resuspended in sterile saline (0.9% NaCl in H 2 O), spread onto glass slides, then air-dried and fixed with 100% methanol.…”
Section: Microscopic Observation Of Bacteriamentioning
confidence: 99%
“…RNA polymerase was also found to copurify with Tn5 transposase, but the copurification was reduced in extracts from a topA mutant strain, suggesting that the interaction between RNA polymerase and DNA topoisomerase I was responsible for the copurification of RNA polymerase with Tn5 transposase (10). The proposed function of topoisomerase I activity in removal of transcription-driven hypernegative supercoiling (8,9) would be greatly facilitated by direct proteinprotein interaction with RNA polymerase.…”
mentioning
confidence: 93%
“…In previous studies, Tn5 transposase was found to copurify with E. coli DNA topoisomerase I and inhibit the topoisomerase I activity (10). RNA polymerase was also found to copurify with Tn5 transposase, but the copurification was reduced in extracts from a topA mutant strain, suggesting that the interaction between RNA polymerase and DNA topoisomerase I was responsible for the copurification of RNA polymerase with Tn5 transposase (10).…”
mentioning
confidence: 99%
“…Overexpressed proteins were purified as described previously (26,36,37). Subunits of gyrase and topo IV were mixed at equimolar concentrations then incubated on ice for 15 min to allow for holoenzyme assembly before assaying.…”
mentioning
confidence: 99%